2017
DOI: 10.1007/s10549-016-4095-2
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 expression and tumor infiltrating PD-1+ lymphocytes associated with outcome in HER2+ breast cancer patients

Abstract: Our data showed the relevance of PD-L1 expression in HER2+ breast cancer. A combined evaluation of PD-L1 and PD-1 TIL in the prognosis of breast cancer might also be of value in treatment prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 42 publications
4
77
2
1
Order By: Relevance
“…PD‐L1 expression evaluated by IHC on untreated primary BC has been associated with both better and poorer clinical outcome. In particular, several authors reported poorer disease‐free survival (DFS)/recurrence‐free survival (RFS) and/or overall survival (OS) in cases of higher PD‐L1 expression on primary BC , especially in the TN subtype . These results seems to be consistent with the previously mentioned correlation between PD‐L1 expression and unfavorable clinicopathological BC features, thus possibly indicating that PD‐L1 expression may be part of the immune evasion process taking place in the context of tumor microenvironment .…”
Section: Methodssupporting
confidence: 77%
“…PD‐L1 expression evaluated by IHC on untreated primary BC has been associated with both better and poorer clinical outcome. In particular, several authors reported poorer disease‐free survival (DFS)/recurrence‐free survival (RFS) and/or overall survival (OS) in cases of higher PD‐L1 expression on primary BC , especially in the TN subtype . These results seems to be consistent with the previously mentioned correlation between PD‐L1 expression and unfavorable clinicopathological BC features, thus possibly indicating that PD‐L1 expression may be part of the immune evasion process taking place in the context of tumor microenvironment .…”
Section: Methodssupporting
confidence: 77%
“…In our present study, no markers, including PD‐1, expressed in TIMC were associated with prognosis. No apparent correlation between PD‐1 expression and prognosis was found in our study although previous studies have shown inconsistent results . In renal cell carcinoma, PD‐1 expression in TIMC was independently associated with poor outcome .…”
Section: Discussionmentioning
confidence: 99%
“…In renal cell carcinoma, PD‐1 expression in TIMC was independently associated with poor outcome . In glioblastoma and Her2 positive breast carcinoma, patients with PD‐L1 positive expression in tumor cell and PD‐1 low expression in TIMC showed worse prognosis . These results indicate that PD‐1 status may be variable in interaction with PD‐L1 status of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reporting no correlation of PD-L1 expression with survival [30,[33][34][35][36][37][38][39], others reporting worse survival [40,41], and some reporting better survival outcomes [36,37]. The association of PD-L1 expression with better overall survival seems counter-intuitive because PD-L1 on tumor cells interact with T cells leading to T cell inactivation and suppression of immunity; perhaps, higher PD-L1 expression is associated with higher levels of TILs, rending high levels of PD-L1 a favorable marker reflecting the strength of the anti-tumor immune response [22,38].…”
Section: Discussionmentioning
confidence: 99%